Analysis of Sumatran Earthquake Coulomb Stress Changes in Geothermal Potential in Rianite, Samosir Regency - Sinaga, Goldberd Harmuda Duva; Nainggolan, Juliper (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
Increasing energy demand and high world oil prices are making countries turn to geothermal energy use. Indonesia is a country that has geothermal energy due to Indonesia's geographical location and geological conditions, which is located between three active earth plates so that Indonesia has 240 volcanoes and often experiences earthquakes. The 2003-2013 earthquake data obtained are coordinates, magnitude, depth, focal mechanism and all these data are analyzed in the coulomb stress method. Rianiate geothermal measurement data in March 2013 included geothermal location, hotspring and air temperature, pH, and geochemical measurements. The analysis results showed that the highest coulomb stress value was at a depth of 90 km of 0.56 bar while the shear and normal values were 0.452 bar and 0.251 bar. The result of the spread of coulomb stress is to the northeast, east and southeast. Then the results of the analysis of the direction of distribution of coulomb stress are compared to the location of the hotspring based on a decrease in temperature, the change in the potential of hotspring 1 leads to hotspring 2, 3, and 4 in the opposite direction, namely northwest or leads to the largest source of colulomb stress, so that Coulomb Stress Changes affect indirectly changes in the geothermal potential of Rianiate